Wind Velocity Decreasing Effects of Windbreak Fence for Snowfall Measurement - Ki-Pyo You; Young-Moon Kim (Advances in Meteorology)
Meteorological observatories use measuring boards on even ground in open areas to measure the amount of snowfall. In order to measure the amount of snowfall, areas unaffected by wind should be found. This study tried to determine the internal wind flow inside a windbreak fence, identifying an area unaffected by wind in order to measure the snowfall. We performed a computational fluid dynamics analysis and wind tunnel test, conducted field measurements of the type and height of the windbreak fence, and analyzed the wind flow inside the fence. The results showed that a double windbreak fence was better than a single windbreak fence for decreasing wind velocity. The double fence (width 4 m, height 60 cm, and fixed on the bottom) has the greatest wind velocity decrease rate at the central part of octagonal windbreak.